How many electric vehicles can the current Australian electricity grid support?. (May 2020) - Li, Mengyu; Lenzen, Manfred
Highlights: Hourly spatio-temporal electricity dispatch is modelled to meet EV load in Australia. EV charging is spatially and temporally optimised using high-resolution GIS data. Current grid can support EVs at 5–10% penetration under uncontrolled charging. Controlled charging increases the ability to accommodate EVs to 60–70% penetration. Controlled charging reduces electricity cost by up to around 4–6%. Abstract: We quantitatively investigate the impact of uncontrolled and controlled charging demand of battery electric vehicles (BEVs) on electricity generation, loss-of-load probability (LOLP), and levelized cost of electricity (LCOE) in Australia. We consider both high- and low-fuel-economy (HE and LE) BEVs, assume BEV penetration rates (EVPR) ranging from 0 to 100%, and three controlled charging participation rates (0%, 53% and 100%). The spatio-temporal distribution of BEV load is estimated by a GIS-based probabilistic model at a high-resolution level for Australia. The BEV charging impact is simulated by an hourly supply-demand model, respecting currently existing installed capacity, operating technologies and LOLP standards, to simulate an electricity dispatch for an entire year. BEV charging is spatially and temporally optimised to achieve minimum levelized cost. We show that the current Australian national grid can support HE and LE BEVs at 5–10% penetration for uncontrolled charging, and around 60–70% for controlled charging. Controlled charging also reduces electricity cost by up to around 4–6%.